Changes in limiting resources determine spatio-temporal variability in tree–grass interactions - Gea-Izquierdo, G.; Montero, G.; Cañellas, I. (Agroforestry Systems, 2009)
Changing biotic and abiotic stress mediate in plant–plant interactions resulting in positive to neutral or negative effects, and these effects can change with gradients of stress or through plant dynamics. Here we studied the variability in annual grass production and composition induced by gradients of intercepted light by trees in years of contrasting precipitation in Mediterranean holm oak open woodlands. Although trees reduce the light radiance received by the pasture community, the presence of trees generally had a positive effect on pasture production in average climatic years where soil fertility was low. However, the interaction changed with increasing abiotic water stress. In a dry year, the increase in fertility could not be utilized and the effect of the crown was neutral. The effect of shade turned out to be beneﬁcial for growth, contrary to the situation in an average climatic year. Light insolation was positive for legume biomass. There was high variability in functional components over the course of the growing period and from 1 year to another. Under low levels of other biotic stresses such as livestock grazing or root competition, the limiting factor among light, soil moisture or soil nutrients may determine whether facilitation or competition occurs.
Keywords: Abiotic stress; competition; Dehesa; Facilitation; Grass production; Mediterranean

Acorn production in Spanish holm oak woodlands - Gea-Izquierdo, G.; Cañellas, I.; Montero, G. (Forest Systems, 2008)
We present a review on the state-of-the-art of fruit prodution in Western Iberia woodlands («dehesas»), and particularly in Q. ilex (holm oak) «dehesas». This threatened ecosystem is of very high ecological and economical importance. Quercus sp. fruits (acorns) are essential for wildlife, and for pig fattening in «dehesas». In the first part of this review we briefly describe the phenology of the holm oak and the factors affecting acorn morphology and chemical composition. In the second half we analyze the main known factors reported in the literature that determine acorn production: pruning, stand characteristics, and site (weather and soil). We make several suggestions to improve future research and detect the existing gaps in the undertanding of acorn production. Fruit production is highly variable, both between and within years and individuals. The mean production in «dehesas» (mean density circa 50 trees/ha) is around 250-600 kg/ha (≈100 g/canopy-m2 , CV> 100%). Acorn morphology is also very variable, with mean sound acorn size around 3.5 × 1.6 cm, CV ≈ 10% (3.5 g/acorn, CV > 50%). Silviculture plays an essential role in acorn production. Acorn production per tree seems to be negatively related to density. The effect of pruning is less clear: production seems to be reduced in the first and second years after pruning. After the third year it is not possible to discern from the literature whether there is any response to pruning or not. Weather and soil (site) also impact production and their effects should be explored in future management. The influence of genetics is unknown and should also be addressed. Longer data series are necessary. The dasometric features of the stands need to be characterized, in order to better understand production and compare results from different locations. Much research is still required to understand the functioning of fruiting in these woodlands.
Keywords: acorn; agrosilvopastoral systems; Dehesa; fruit production; Holm oak; Quercus ilex

Generalized height-diameter and crown diameter prediction models for cork oak forests in Spain - Sánchez-González, M.; Cañellas, I.; Montero, G. (Investigación Agraria: Sistemas y Recursos Forestales, 2007)
A generalized height-diameter equation, along with a crown diameter prediction equation for cork oak forests in Spain were developed based on data from the Second Spanish Forest Inventory. Nine generalised height-diameter equations were selected as candidate functions to model the height-diameter under cork relationship, while for the crown diameter prediction model five linear and non-linear equations were tested. The equations were fitted using the mixedeffects model approach. The Stoffels & Van Soest power equation, constrained to pass through the point of dominant diameter and dominant height, was selected as the generalised height-diameter model. Regarding the crown diameter prediction model, the parable function without the intercept and with quadratic mean diameter incorporated as a fixed effect into the b parameter, proved to be the model with best prediction capabilities. The models were validated by characterising the model error using the PRESS (Prediction Sum of Squares) statistic. Both equations will be submodels of the ALCORNOQUE v1.0, a management oriented growth and yield model for cork oak forests in Spain.
Keywords: crown width; forest growth modelling; height-diameter relationship; mixed effects models; Quercus suber